Dataset for Potential of Agricultural Expansion in Degraded Pasture Lands in Brazil based on Geospatial Databases. - Victoria, Daniel de Castro (2024)
This is the final data (raster and tabulated forms) from our analysis which evaluates the Agricultural Potential for pasture areas in Brazil, according to their vegetative vigor and degradation evidence. These results were used in the "Potential of Agricultural Expansion in Degraded Pasture Lands in Brazil based on Geospatial Databases" study.